An Analysis of a Commercial Database on the Use of Erectile Dysfunction Treatments for Men With Employer-Sponsored Health Insurance - Burnett, Arthur L.; Rojanasarot, Sirikan; Amorosi, Stacey L. (Urology (Ridgewood, N.J.), 2021)
To investigate the annual erectile dysfunction (ED) prevalence among men enrolled in an employer-sponsored health insurance (ESHI) plan and evaluate ED treatment profiles among those with an ED diagnosis. A cross-sectional claims analysis was conducted using the IBM MarketScan Commercial Database, a nationally representative sample of US workers enrolled in ESHI plans. Patients aged 18-64 with at least one ED medical diagnosis claim and continuous enrollment in a given year between 2009 and 2017 were included. Among those with an ED diagnosis, utilization rates of the following ED treatments were determined: phosphodiesterase type 5 inhibitors (PDE5I), penile prosthesis implantation, other ED treatments (eg, vacuum pump, intraurethral suppositories), combination treatment, and no insurer-paid treatments. Between 2009 and 2017, the annual prevalence of men with ESHI suffering from ED increased by 116%. However, in 2017, only 23% of men with an ED diagnosis received an ED therapy paid for by their ESHI plans. The proportion of men taking PDE5Is ranged from 18% in 2012 to 26% in 2015. The proportion of men with ED undergoing penile prosthesis implantation has declined in recent years (0.23% in 2009 to 0.11% in 2017). Similarly, the rate of men who received other ED treatments or combination treatment has decreased from 2009 to 2017 (0.94%-0.30% and 0.65%-0.19%, respectively). ED prevalence among men insured by an ESHI plan has notably increased, yet approximately three-quarters of these men had no claims for ED treatments, indicating substantial access gaps to treatment.